The eATP/P2×7R Axis Drives Quantum Dot‐Nanoparticle Induced Neutrophil Recruitment in the Pulmonary Microcirculation - Chenxi Li; Qiongliang Liu; Lianyong Han; Haiyun Zhang; Roland Immler; Birgit Rathkolb; Judith Secklehner; Martin Hrabe deAngelis; Ali Önder Yildirim; Dagmar Zeuschner; Annette Nicke; Leo M. Carlin; et al. (Advanced Science)
Abstract Exposure to nanoparticles (NPs) is frequently associated with adverse cardiovascular effects. In contrast, NPs in nanomedicine hold great promise for precise lung‐specific drug delivery, especially considering the extensive pulmonary capillary network that facilitates interactions with bloodstream‐suspended particles. Therefore, exact knowledge about effects of engineered NPs within the pulmonary microcirculation are instrumental for future application of this technology in patients. To unravel the real‐time dynamics of intravenously delivered NPs and their effects in the pulmonary microvasculature, we employed intravital microscopy of the mouse lung. Only PEG‐amine‐QDs, but not carboxyl‐QDs triggered rapid neutrophil recruitment in microvessels and their subsequent recruitment to the alveolar space and was linked to cellular degranulation, TNF‐α, and DAMP release into the circulation, particularly eATP. Stimulation of the ATP‐gated receptor P2X7R induced expression of E‐selectin on microvascular endothelium thereby mediating the neutrophilic immune response. Leukocyte integrins LFA‐1 and MAC‐1 facilitated adhesion and decelerated neutrophil crawling on the vascular surface. In summary, this study unravels the complex cascade of neutrophil recruitment during NP‐induced sterile inflammation. Thereby we demonstrate novel adverse effects for NPs in the pulmonary microcirculation and provide critical insights for optimizing NP‐based drug delivery and therapeutic intervention strategies, to ensure their efficacy and safety in clinical applications.